Understanding Healthcare-Seeking Pathways and Dilemmas Among Women with Obstetric Fistulas in Ethiopia: A Qualitative Inquiry - Hurissa BF; Koricha ZB; Dadi LS (Dove Medical Press, 2023)
Bekana Fekecha Hurissa,1 Zewdie Birhanu Koricha,2 Lelisa Sena Dadi3 1School of Midwifery, Institute of Health, Jimma University, Jimma, Ethiopia; 2Department of Health, Behavior, and Society, Faculty of Public Health, Jimma University, Jimma, Ethiopia; 3Department of Epidemiology, Faculty of Public Health, Jimma University, Jimma, EthiopiaCorrespondence: Bekana Fekecha Hurissa, Email bekf@rocketmail.comBackground: Obstetric fistula is a public health problem with a damaging effect on the health of women around the world. The path to medical care is an integral part of women's experience of illness that may have an impact on their health. Studies have addressed the experiences of patients after fistula repair, but fistula victims' care-seeking pathways and dilemmas are still poorly understood in low-income countries, particularly Ethiopia.Objective: This study aimed to explore the care-seeking pathways and dilemmas among women with fistulas in Ethiopia.Methods: An exploratory phenomenological study was carried out from April 1 to August 1, 2019, through in-depth interviews and supplementary informant interviews. Data were obtained from 21 purposively selected women with fistulas who survived with morbidity for one and more years and 12 supplementary interviewees at fistula treatment centers in Oromia Region and Addis Ababa. Data were analyzed assisted by ATLAS. ti 8.4 software.Results: Respondents gave their testimony that most of the women with fistulas first sought care from traditional care places and finally from fistula treatment centers. The reasons for care-seeking path dilemmas were a wrong perception about fistula, its causes, and treatment; families' pressure and lack of decision-making power on where to seek treatment, and a lack of knowledge on where modern treatments are available for fistula. They received psychological, companionship, and transport support from a family and a community; referral and counseling support from health care providers during their care-seeking pathways.Conclusion: A myriad of reasons inhibits the right care-seeking pathways among women with fistulas. Communities and women with fistula awareness creation on the right places for fistula treatment and psychological support programs are required. Additionally, developing and implementing tactics for community-level screening programs for targeted victims and early admission to treatment centers can minimize the tragic sequela of the fistula.Keywords: obstetric fistula, care-seeking pathways, women with fistula, dilemma, Ethiopia